A randomized, placebo‐controlled study of the pharmacokinetics, pharmacodynamics, and tolerability of the oral JAK2 inhibitor fedratinib (SAR302503) in healthy volunteers. (16th November 2013) - Zhang, Meng; Xu, Christine R.; Shamiyeh, Elias; Liu, Feng; Yin, Jian Y.; von Moltke, Lisa L.; Smith, William B.
Abstract Fedratinib (SAR302503/TG101348) is a Janus kinase 2 (JAK2)‐selective inhibitor in clinical development for the treatment of myelofibrosis. In this randomized, placebo‐controlled, Phase 1 study, the pharmacokinetics, pharmacodynamics and tolerability of ascending single doses of fedratinib (10–680 mg) were assessed in healthy male subjects. Fedratinib was rapidly absorbed, with peak plasma concentration observed approximately 3 hours after dosing. The mean terminal half‐life of fedratinib was approximately 67 hours, which was unaffected by dose. Fedratinib exposure increased in a greater than dose‐proportional manner. Suppression of signal transducer and activator of transcription 3 (STAT3) phosphorylation, indicative of JAK2 inhibition, was observed at 3 hours post‐dose for subjects in the 300, 500, and 680 mg groups, with the level of suppression increasing with dose. The relationship between fedratinib exposure and suppression of STAT3 phosphorylation was described using an inhibitory effect sigmoid Emax model, with an EC50 of 1, 210 ng/mL in healthy subjects. The most common adverse events were mild gastrointestinal toxicities.